Does Sleep Position Influence Sleep-Disordered Breathing in Infants With Cleft Palate: A Feasibility Study?. (February 2022) - Murray, Clare S.; Walsh, Tanya; Bannister, Trisha; Metryka, Aleksandra; Davies, Karen; Lin, Yin Ling; Williamson, Paula; Callery, Peter; O'Brien, Kevin; Shaw, William; Bruce, Iain; ,
Objective: Cleft palate (CP) can affect breathing, leading to sleep-disordered breathing (SDB). Sleep position can affect SDB, but the optimum sleep position for infants with CP is unknown. We aimed to determine the design of a pragmatic study to investigate the effect of the 2 routinely advised sleep positions in infants with CP on oxygen saturations. Design: A multicentered observational cohort. Setting: Four UK-based cleft centers, 2 advising supine- and 2 side-lying sleep positions for infants with CP. Participants: Infants with isolated CP born July 1, 2015, and December 31, 2016. Of 48 eligible infants, 30 consented (17 side-lying; 13 supine). Interventions: Oxygen saturation (SpO2 ) and end-tidal carbon dioxide (ETCO2 ) home monitoring at age 1 and 3 months. Qualitative interviews of parents. Outcome Measures: Willingness to participate, recruitment, retention, and acceptability/success (>90 minutes recording) of SpO2 and ETCO2 monitoring. Results: SpO2 recordings were obtained during 50 sleep sessions on 24 babies (13 side-lying) at 1 month (34 sessions >90 minutes) and 50 sessions on 19 babies (10 side-lying) at 3 months (27 sessions >90 minutes). The ETCO2 monitoring was only achieved in 12 sessions at 1 month and 6 at 3 months; only 1 was >90 minutes long. The ETCO2 monitoring was reported by the majority as unacceptable. Parents consistently reported the topic of sleep position in CP to be of importance. Conclusions: This study has demonstrated that it is feasible to perform domiciliary oxygen saturation studies in a research setting and has suggested that there may be a difference in the effects of sleep position that requires further investigation. We propose a study with randomization is indicated, comparing side-lying with supine-lying sleep position, representing an important step toward better understanding of SDB in infants with CP.